Computer Organization and Design : The Hardware / Software Interface - Patterson, David A. : John L. Hennessy (New York: Morgan Kaufmann, 2009)
Computer Science
Keywords: Computer organization; Computer design; Hardware; Software; Computer interfaces; Multiprocessor